Uterine Serosal Inclusion Cysts with Greater Omentum Involvement in a Cat. (November 2022) - Kaya, Muhammed T.; Kuruca, Nilufer; Kanat, Mustafa; Akca, Fatma B.; Gulbahar, Mustafa Y.
Summary: A 7-year-old nulliparous Chinchilla queen was admitted to a veterinary clinic for routine ovariohysterectomy. Examination of the uterus, greater omentum and varicose ovarian veins revealed multiple thin-walled cysts filled with a transparent fluid over the serosal surfaces of these organs. Histologically, the cysts were of variable size, filled with a small amount of mucinous fluid, and had thin walls that contained hypocellular collagen and a few small calibre vessels. The inner and outer epithelium of the cyst walls and the cells that lined the uterine serosa were immunopositive for cytokeratin and vimentin, suggesting a mesothelial origin. Alpha-smooth muscle actin immunolabelling was patchy or continuous in smooth muscle in the wall of many of the cysts.